Science Mapping of Library and Information Science (LIS) and Library Technology Studies in Indonesia - Kamaludin Kamaludin; Abdurachman Prasetyadi (Al-Ma'mun, 2023)
This study aims to map the knowledge of the Library and Information Science (LIS) study and its technology in Indonesia. Data were obtained from the Scopus database by entering keywords in the title: library; library science; technology libraries; and Indonesia, during 1974-2022 and received 87 documents. The method used was bibliometric, with Bibliometric and CiteSpace software. The results showed that the annual growth of LIS studies in Indonesia was still relatively low at 3.41%, and the highest average citations occurred in 2013. Indonesia dominated authors with the highest citations, and the most relevant sources were dominated by proceedings showing that the LIS study was still in its infancy, a less scientific research stage. Most cited journal articles in references. Indonesia was the country with the most frequency of collaboration, namely 21 collaborations. The keyword library was the most commonly used 349 times, then the technical terms that emerged included information system (5%), search engine (2%), automation, and big data, respectively (1%). Cluster #0 public library was the largest, and this cluster includes a smart public library, smart library, and smart environment in its cluster members.